Honored and dishonored guests : westerners in wartime Japan - Brecher, W. Puck (Harvard East Asian monographs ;, 2017)
"Recovers and chronicles Western communities in wartime Japan and uses that body of experiences to reconsider allegations of Japanese racism and racial hatred. The book's accounts of stranded Westerners yield a unique interpretation of race relations and wartime life in Japan"--